Clinical Evaluation of Composite Restorations with and without Polyethylene Fiber in First Permanent Molars: A 24-Month Randomized Clinical Trial - Semanur Özüdoğru; Gül Tosun (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the 24-month clinical performance of composite resin restorations with and without polyethylene fiber in the first permanent molars of pediatric patients with extensive caries. Material and Methods: In total, 75 Class II restorations were placed in the permanent molar teeth of 75 children (mean age 11.3 years) with (FC; n=38) or without (C; n=37) fiber. One operator placed all the restorations. The restorations were evaluated using the modified USPHS criteria in terms of retention, color match, marginal discoloration, anatomic form, marginal adaptation, secondary caries, and postoperative sensitivity. Statistical data were analyzed using chi-square and Cochran tests (p<0.05). Results: At the end of two years, 65 restorations (FC:31; C:34) were followed up. No changes were observed during the first six months. After 24 months of follow-up, there were minor changes in marginal adaptation and marginal color in both groups; however, no statistically significant difference was observed between the clinical performances for all criteria (p>0.05). Conclusion: Extensive composite restorations with or without fibers displayed good clinical performance in high load-bearing areas after 24 months.